2002
DOI: 10.1152/japplphysiol.00977.2001
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal expression of neurotransmitters, receptors, and cytochrome oxidase in the rat pre-Bötzinger complex

Abstract: Liu, Qiuli, and Margaret T. T. Wong-Riley. Postnatal expression of neurotransmitters, receptors, and cytochrome oxidase in the rat pre-Bötzinger complex. J Appl Physiol 92: 923-934, 2002; 10.1152/japplphysiol.00977.2001.-The preBötzinger complex (PBC) is postulated as the center of respiratory rhythmogenesis. Previously, we found a reduction or plateau of cytochrome oxidase (CO) activity in the PBC and other respiratory nuclei at postnatal days 3-4, despite a general increase of CO with age, suggesting a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
120
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(142 citation statements)
references
References 53 publications
(57 reference statements)
19
120
3
Order By: Relevance
“…We found that, against a general increase in CO with age from postnatal days (P) 0-21, there was a plateau or reduction of CO activity on P3-P4 and a dramatic drop of enzyme levels on P12 (22,24). This was accompanied by a concomitant decrease in excitatory neurotransmitter glutamate and its N-methyl-D-aspartate receptor subunit 1 and an increase in inhibitory neurotransmitters GABA, its receptors (GABA B ), and glycine receptors.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…We found that, against a general increase in CO with age from postnatal days (P) 0-21, there was a plateau or reduction of CO activity on P3-P4 and a dramatic drop of enzyme levels on P12 (22,24). This was accompanied by a concomitant decrease in excitatory neurotransmitter glutamate and its N-methyl-D-aspartate receptor subunit 1 and an increase in inhibitory neurotransmitters GABA, its receptors (GABA B ), and glycine receptors.…”
mentioning
confidence: 87%
“…This was accompanied by a concomitant decrease in excitatory neurotransmitter glutamate and its N-methyl-D-aspartate receptor subunit 1 and an increase in inhibitory neurotransmitters GABA, its receptors (GABA B ), and glycine receptors. The glutamate receptor GluR2, which reduces the permeability of DL-␣-amino-3-hydroxy-5-methylisoxazolepropionic acid receptors to Ca 2ϩ and thereby reduces neuronal excitation, also exhibited an increase during those two periods (22). These findings suggest that, during postnatal development of the rat, there may be two critical periods, P3-P4 and especially P12, when its respiratory system may be under a stronger inhibitory than excitatory drive and may render the animal more vulnerable to respiratory insults.…”
mentioning
confidence: 99%
“…The monoclonal mouse antibody bd-17 (US Biological, bovine, cat # G1016; 1:400) directed against both ␤2 and ␤3 subunits of GABA A Rs, recognize the major GABA A R subtypes in the CNS (McKernan and Whiting, 1996) expressed during postnatal development (Alvarez et al, 1996) and in adult spinal cord motoneurons (Fritschy et al, 1994;Bohlhalter et al, 1996). The mature form of the GlyR, GlyR␣1, was detected with either the monoclonal antibody mAb2b (Connex, mouse, 1:80, catalog # 28 120 501-0 and Synaptic Systems (SySy), mouse 1:250, catalog # 146 111) or the polyclonal antibody pAb2b (Millipore Bioscience Research Reagents, rabbit, 1:100; catalog # AB5052), depending on the other primary antibodies used for double immunofluorescence staining (Pfeiffer et al, 1984;Schröder et al, 1991;Liu and Wong-Riley, 2002;Baer et al, 2003). Both monoclonal or the polyclonal antibodies against GlyR␣1 displayed punctuate fluorescence outlining the cell bodies and dendrites of motoneurons, and a quantitative analysis showed 95% colocalization of the fluorescent clusters when using both antibodies (Lorenzo et al, 2007).…”
Section: Antibodies and Their Dilutionsmentioning
confidence: 99%
“…2c,f ), and preBötC (Fig. 2d,g,h) (Horie et al, 2000;Liu and Wong-Riley, 2002;Pagliardini et al, 2003). To further correlate the internalization of TMR-SubP with NK1R expression, treated slices were processed for immunohistochemical detection of NK1R.…”
Section: Diffusion and Internalization Of Tmr-subp In Medullary Slicesmentioning
confidence: 99%